Innovations in Librarianship: Improving Reading Interest Through Public Administration Strategies: Inovasi dalam Kepustakawanan: Meningkatkan Minat Baca Melalui Strategi Administrasi Publik - Yanuar Rokhima A; Ilmi Usrotin Choiriyah; Luluk Farida; Sebrina Cahya K.A; Eri Sabrina; Indira Sari (Proceedings of The ICECRS, 2025)
General Background Education in the globalization era demands enhanced human resource quality and robust literacy competencies to support active societal participation. Specific Background School libraries operate as vital learning hubs, whereas librarians implement promotional activities, reading motivation initiatives, and teacher collaborations to foster student literacy. Knowledge Gap Despite these institutional provisions, empirical realities at SMKN 3 Buduran Sidoarjo reveal low student reading motivation, minimal library utilization by subject teachers, and technical disruptions such as internet connectivity issues. Aims This qualitative case study analyzes the role of librarians in supporting the teaching and learning process and increasing reading interest. Results Findings demonstrate that librarians successfully execute literacy socialization, maintain diverse service provisions, and arrange attractive spaces, yielding general student satisfaction, though low reading motivation and technical barriers persist. Novelty This research specifically identifies the intersection between proactive school librarianship strategies and structured administrative teacher collaboration within vocational educational environments. Implications Strengthening institutional literacy culture necessitates comprehensive support from all relevant stakeholders alongside structured collaborative programs that integrate the library directly into core academic curricula. Highlights: Proactive literacy outreach and attractive spatial organization successfully generate high student satisfaction with available library services. Vocational students predominantly exhibit low reading motivation while frequently utilizing physical library spaces for relaxation and connectivity access. Establishing structured cooperative programs between librarians and subject teachers remains essential for fully integrating institutional information resources. Keywords: The Role Of Librarians, Interest In Reading, School Libraries, Public Administration Strategies, Literacy Innovations